Preferred synthesis of armchair transition metal dichalcogenide nanotubes - Abid; Luneng Zhao; Ju Huang; Yongjia Zheng; Yuta Sato; Tianyu Wang; Dmitry Levshov; Lingfeng Wang; Qingyun Lin; Zhen Han; Chunxia Yang; Bill Herve Nduwarugira; et al. (Science, 2026)
Nanotubes represent an important class of crystalline materials but controlling their structures, particularly chiralities, remains a fundamental challenge. In this work, we report a strategy for synthesizing transition-metal dichalcogenide nanotubes with preferred armchair chirality. tin disulfide, molybdenum disulfide, and tungsten disulfide nanotubes are formed with high yield and structural purity inside boron nitride nanotube channels. Atomic-resolution imaging, electron diffraction, and circular dichroism reveal an armchair preference up to 83%. Density functional theory rules out structural stability as the origin of this preference but confirms that zigzag nanoribbons are energetically more stable. Machine learning potential molecular dynamics simulate that zigzag nanoribbons roll up to form armchair nanotubes, a process that is subsequently observed by in situ transmission electron microscope. This work may inspire the achievement of on-demand synthesis of various nanotubes with specific chiralities.